What is counterterrorism for? - Jackson, Leonie B. (What is it for?, 2025)
Terrorism will always be frontpage news - counterterrorism is often discussed as an afterthought, yet it is vitally important to understand what is done in the name of our safety. Since 9/11, there has been a huge ramping up of the state’s special powers in the name of security, such as indefinite detention, the assassination of suspected terrorists, the use of extraordinary rendition, torture, and changes to due process. However, these powers are often shadowy, they are rarely rolled back, and they can be counterproductive. This book focuses on understanding the costs of counterterrorism and asking how they can be reduced; global in scope, it looks not just at Western liberal democracies, but at numerous examples from across the world.